Granger Causality and Hierarchical Transmission Patterns in BRICS Currency Markets - Mala, Chajar Matari Fath; Jumono, Sapto (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The short-run causal links and the multistage transmission order among BRICS (Brazil, Russia, India, China, and South Africa) currencies against the US dollar are studied from November 2019 to May 2025. We utilise daily exchange rate returns and employ a multinivariate VAR-Granger causality framework with a lag length of eight to account for short-run interactions during periods encompassing multiple global shocks, such as the COVID-19 pandemic and the Russia-Ukraine war. The pre-estimation diagnostics (ADF unit root test, stability checks and LM serial correlation tests) are strong evidence of the soundness of the model. Granger causality tests, on the other hand, reveal a specific asymmetric, hierarchical structure. A set of players, including the Russian ruble (RUB) and the Indian rupee (INR), are primarily transmitting shocks. At the same time, a second group, e.g., featuring the Chinese yuan (CNY) and South African rand (ZAR), acts as a shock absorber. This novel contribution to the literature uncovers short-run causality behaviors in BRICS forex markets during a previously unprecedented multi-crisis period. It offers new insights into the foreign exchange policy coordination and exchange risk management.